CATALYTIC HYDROTHERMAL LIQUEFACTION OF BOTRYOCOCCUS BRAUNII: ENHANCING BIO-CRUDE OIL YIELD AND QUALITY - Laras Prasakti; Arief Budiman; Said Hanief (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Indonesia's high population density has led to a rapidly growing energy demand. In response, the government is compelled to increase energy production. However, the scarcity of natural resources in the country has prompted the development of alternative energy sources, particularly biomass. Advances in biomass conversion technology have now reached the third generation, which offers the benefit of not competing with food supply. Among the most promising third-generation biomass sources is microalgae. One effective method for converting microalgae into bio-oil is catalytic hydrothermal liquefaction (HTL). This technique enhances both the yield and quality of bio-oil, potentially making its properties comparable to those of crude oil. The present study investigates the influence of catalyst addition in the HTL process on the characteristics of the resulting bio-crude oil. Experiments were conducted using a batch reactor with a silica-alumina catalyst, at different temperatures (200°C, 225°C, and 250°C) and catalyst loadings (4%, 5%, and 6%). The catalytic HTL process produced four distinct product phases: bio-oil, aqueous phase, gas, and solid residue. Analysis using Gas Chromatography–Mass Spectrometry (GC-MS) revealed that the highest hydrocarbon content nearly 40% was obtained with the addition of 6% catalyst. Additionally, increasing catalyst loading was found to improve bio-oil quality.